Audio-Visual Aids in Teaching-Learning Process of Health Science Students and Professionals - Yadav, Prem Kumar; Bera, Tushar Kanti; Mukharjee, Prithwiraj; Yadav, Shankar; Sah, Sanjay Kumar; Kar, Sanjit Kumar (Journal of Universal College of Medical Sciences, 2015)
Essence and necessity to make the teaching-learning process more innovative, scientific and students' centred have become main aim and objective of present day education system. A large number of methods are being used in teaching-learning process. The audio visual aids are being increasingly used since these involve both audio (verbal) as well as visual way of teaching. Several researches have been proved that the ability to recall is high with teaching using audio visual aids. Selection of appropriate media of teaching is one of the smart and important steps of teaching students of different levels and domains. Several media of audio visual aids are being practisized such as overhead projector (OHP), power point presentation (PPT), white or black board teaching and flip charts etc. These media have merits as well as demerits. There are key techniques to make them more effective. The audio visual aids help in consolidation of long term memories of learnt information. Logical use of different types of media simultaneously during teaching can be more beneficial for the learners in many ways.